If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7n + -11 = 5n + 7 Reorder the terms: -11 + 7n = 5n + 7 Reorder the terms: -11 + 7n = 7 + 5n Solving -11 + 7n = 7 + 5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5n' to each side of the equation. -11 + 7n + -5n = 7 + 5n + -5n Combine like terms: 7n + -5n = 2n -11 + 2n = 7 + 5n + -5n Combine like terms: 5n + -5n = 0 -11 + 2n = 7 + 0 -11 + 2n = 7 Add '11' to each side of the equation. -11 + 11 + 2n = 7 + 11 Combine like terms: -11 + 11 = 0 0 + 2n = 7 + 11 2n = 7 + 11 Combine like terms: 7 + 11 = 18 2n = 18 Divide each side by '2'. n = 9 Simplifying n = 9
| 5-2thirdsx=-6 | | y=-5x^2-10x-13 | | -(9c-r)= | | 5p-11=39 | | 7*k=10+x | | -v+5+6v=1+5v+3 | | 6+2p=24 | | g+9=16 | | 6x+19=3x+13 | | y-(-9)=12 | | 18x+8x-13x= | | -(-8m+k)= | | v.19.3=96.5 | | 6b-4=-22 | | w=4+3** | | x-x^2=20 | | 3(w-9)=2(w-8) | | 21=13+q | | 71-(3x+15)=3x(x+7)+x | | 2(x+7)-(-2x-1)=3x | | 4(4m-3)-1(m-5)=-52 | | -(56x-12)= | | 6y-87=7y | | -3=14+x | | 5c-3=6c | | -64=6b-4 | | 2n-7=5n-10 | | 13-3(5x-4)=-2 | | 6x+48=8x+8 | | -4x-5x=27 | | -64=6b | | 1568/7.28=h |